Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Konsumtif Pegawai (Studi Kasus Pada Spbu 61.707.01 61.707.01 Banjarbaru) - Akhmad . Samhudi; Siti Raisa Rizki Pardani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to examine: (1) financial literacy affects consumptive behavior in gas station employees 61.707.01 Banjarbaru, (2) lifestyle affects consumptive behavior in gas station employees 61.707.01 Banjarbaru, (3) financial literacy and lifestyle influence the consumptive behavior of gas station employees 61.707.01 Banjarbaru.                   The design of this research is quantitative research and is a survey research. The research population is all employees of SPBU 61.707.01 Banjarbaru and a sample of 20 respondents with Multiple Linear Regression data analysis.           The result showed: (1) financial literacy had an effect on consumptive behavior in SPBU 61.707.01 Banjarbaru employees, (2) lifestyle had no effect on consumptive behavior in SPBU 61.707.01 Banjarbaru employees, (3) financial literacy and lifestyle had no significant effect, on consumptive behavior in gas station employees 61.707.01 Banjarbaru.